Bis(acetato-kappa O-2,O `)diphenyl(pyridine-kappa N)tin(IV) - Khaledi, H.; Ali, H.M.; Abdulla, M.A. (International Union of Crystallography, 2010)
The asymmetric unit of the title compound, [Sn(C6H5)(2)-(C2H3O2)(2)(C5H5N)], contains two crystallography independent molecules. In both molecules, the Sn-IV atom is sevencoordinated in a distorted pentagonal-bipyramidal geometry with the two phenyl groups in axial positions. The two molecules differ mainly in the torsion of the phenyl and pyridine rings. The dihredral angles between the phenyl rings are 89.54 (15)and 60.11 (14)degrees in the two molecules while the dihedral angles between the pyridine rings and the acetate groups are 12.6 (2)and 41.77 (13)degrees in the two molecules.